Eye movement activity in normal human fetuses between 24 and 39 weeks of gestation - Okawa, Hikohiro; Morokuma, Seiichi; Maehara, Kana; Arata, Akiko; Ohmura, Yoshiyuki; Horinouchi, Takashi; Konishi, Yukuo; Kato, Kiyoko (PLOS ONE, 2017)
Rapid eye movement (REM) sleep occurs throughout a relatively large proportion of early development, and normal REM activity appears to be required for healthy brain development. The eye movements (EMs) observed during REM sleep are the most distinctive characteristics of this state. EMs are used as an index of neurological function postnatally, but no specific indices of EM activity exist for fetuses. We aimed to identify and characterize EM activity, particularly EM bursts suggestive of REM periods, in fetuses with a gestational age between 24 and 39 weeks. This cross-sectional study included 84 normal singleton pregnancies. Fetal EMs were monitored using real-time ultrasonography for 60 min and recorded as videos. The videos were manually converted into a time series of EM events, which were then analyzed by piecewise linear regression for various EM characteristics, including EM density, EM burst density, density of EMs in EM bursts, and continuous EM burst time. Two critical points for EM density, EM burst density, and density of EMs in EM bursts were evident at gestation weeks 28–29 and 36–37. Overall EM activity in human fetuses increased until 28–29 weeks of gestation, then again from 36–37 to 38–39 weeks of gestation. These findings may be useful for creating indices of fetal neurological function for prognostic purposes.